2005
DOI: 10.1149/1.1828352
|View full text |Cite
|
Sign up to set email alerts
|

Methanol Sensor Operative in Wide Range of Fuel Concentration and Temperature with Fast Response

Abstract: An electrochemical methanol sensor for monitoring the fuel concentration in direct methanol fuel cells was constructed using a thin composite membrane as the electrolyte. The 6 m thick composite membranes were prepared by impregnating porous polyethylene-terephthalate film with Nafion ionomer. The resulting sensor is capable of monitoring the fuel in any concentration up to pure methanol. This can be accomplished by placing a palladium film at the interface between the anode and the membrane. The sensor is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Additional compensation is needed for situations that are varying. The electrolytic type sensing schemes measure the limiting current or the half-cell potential to establish the relationship with methanol concentration [11][12][13][14][15]. In these designs, a substantial sensor is required while the reactions wherein are not spontaneous.…”
Section: Introductionmentioning
confidence: 99%
“…Additional compensation is needed for situations that are varying. The electrolytic type sensing schemes measure the limiting current or the half-cell potential to establish the relationship with methanol concentration [11][12][13][14][15]. In these designs, a substantial sensor is required while the reactions wherein are not spontaneous.…”
Section: Introductionmentioning
confidence: 99%
“…For monitoring the methanol concentration electrochemical methods are known for their simplicity in design and operation and also for their highly sensitive response to the concentration. The previous work in this laboratory has demonstrated that the sensor is capable of monitoring the fuel in any concentration up to pure methanol 2) .…”
mentioning
confidence: 98%
“…But it is also proposed that the fuel of very high concentration may render more efficient performance to the system. Our group has been engaged in developing the sensor with the aim of fast response, the capability of monitoring wide range of the concentration, and accuracy of the sensing [1][2] . For monitoring the methanol concentration electrochemical methods are known for their simplicity in design and operation and also for their highly sensitive response to the concentration.…”
mentioning
confidence: 99%
“…For most DMFC systems the required concentration is in the range of 0.1-2M. Our group has been engaged in developing electrochemical methanol sensor with the aim of fast response, the capability of monitoring wide range of the concentration, and accuracy of the sensing [1][2] . For monitoring the methanol concentration electrochemical methods are known for their simplicity in design and operation and also for their highly sensitive response to the concentration.…”
mentioning
confidence: 99%